Efeitos antioxidante, anti-inflamatório e antinocicpetivo do isopropóxi-carvacrol em roedores - Bomfim, Rangel Rodrigues (2013)
Previous studies have shown that monoterpenes, compounds mainly presented in essential oils, as well as some synthetic derivatives, have important pharmacological actions. Isopropoxy-carvacrol (IPC) is a new synthetic derivative, which was obtained from carvacrol and its pharmacological properties have not yet been investigated. The aim of this study was to analyze the antioxidant, anti-inflammatory and antinociceptive proprieties of IPC. In order to investigate the antioxidant activity, the nitric oxide scavenger activity and the inhibitory effect on the lipid peroxidation induced by FeSO4 or FeSO4+H2O2 in lipossome preparation were measured in vitro. For the in vivo evaluation, mice (25-30 g) and rats (150-230 g) were used. These animals received the administration of IPC at the doses of 10, 30 or 100 mg/kg or vehicle (Tween 80, 0.5%) by the intraperitoneal route (i.p.), 30 minutes before the experiments, or at the doses of 0.3-3 mg/ear, applied topically during the induction (in the case of mice ear edema test). The nociceptive parameters evaluated were the licking/biting time induced by formalin and the hyperalgesia induced by carrageenan, both injected in the mice paw. The inflammatory parameters evaluated were the rat paw edema induced by carrageenan, the mice ear edema induced by TPA (accompanied by the myeloperoxidase activity measurement in the ears) and leukocyte migration induced by carrageenan to the mice pleural cavity. We also assessed the locomotor activity of mice in the open field and the cytotoxicity of IPC in murine peritoneal macrophages. As the results of this study, IPC showed antioxidant activity in concentrations varying from 100 pg/mL to 100 g/mL. Additionally, the pre-treatment with IPC reduced the licking/biting time of the mice paws, both in the first and second phases of the formalin-induced nociception, respectively at the doses of 100 mg/kg or 30 and 100 mg/kg, when compared with the vehicle-treated group. In the assessment of carrageenan-induced hyperalgesia, the dose of 100 mg/kg of IPC was able to reduce the nociceptive threshold response at the time points of 1 h and 3 h after induction, when compared with the vehicle group. Besides, the administration of IPC did not affect the locomotor activity of mice in the open field test. In rats, the administration of IPC at the dose of 100 mg/kg significantly diminished the carrageenan-induced paw edema, when compared with the vehicle group. No antiedematogenic effect was observed by the local administration of IPC in the TPA-induced mice ear inflammation test, however, the myeloperoxidase activity was significantly decreased in the ears by the simultaneous application of IPC (0.3, 1 or 3.0 mg/ear). In the mice pleurisy induced by carrageenan, the dose of 100 mg/kg of IPC significantly reduced the number of total leukocytes and mononuclear cells found in the pleural cavity, when compared with the vehicle treated group, without altering the number of polymorphonuclear cells. Moreover, the IPC concentrations ranging from 0.1 to 100 g/mL did not affect the peritoneal macrophages viability. These results demonstrate that IPC has antioxidant, anti-inflammatory and antinociceptive activities, which enable future studies directed to the investigation of the mechanisms underlying the pharmacological effects of IPC and may contribute for the development of new drugs for the treatment of inflammation and pain.